Surgical telehealth in medical education: a qualitative contribution that invites a mixed-methods approach - Millan Hernandez, Manuel; Albarrán Pérez, Daniela Francelia (Spanish Journal of Medical Education, 2025)
This letter to the editor reflects on the recently published article titled “Telehealth and the teaching of surgery: creation of an open-access surgical multimedia repository.” The qualitative contribution of the study is recognized, particularly its ability to explore students’ and faculty members’ perceptions of telehealth as a teaching strategy during the pandemic. The instructional design grounded in the Cognitive Theory of Multimedia Learning is highlighted as a key strength, along with the contextual implementation of the VTQ UNAH 101 repository. However, it is suggested that the study’s scope could be expanded through an exploratory sequential mixed-methods design that complements interpretive analysis with quantitative measurements. Finally, the letter underscores the strategic importance of telehealth in Latin America as a tool to reduce educational inequities and strengthen clinical training in structurally limited settings. The letter offers a constructive critical perspective informed by expertise in medical education and mixed-methods research.